Analyses of Steel Bridge Circular Columns using Fiber Model considering Local Buckling - Kinoshita, K. (Institute of Research and Community Outreach - Petra Christian University, 2014)
One of the most concerned problems for analytical estimation of ultimate strength and ductility of steel bridge columns is the consideration of local buckling. Stress-strain curves with softening behavior to include local buckling in fiber model analysis method were proposed by several researchers. However, accuracy of those models is still relatively low. As a consequence, most steel bridge designs have been done using fiber model analysis method without consideration of local buckling. In order to improve the analytical response estimation of steel bridge columns, a fiber model analysis method considering local buckling is proposed in this study. In this method, multi-fiber elements were used to model the local buckling length to simulate local buckling deformation. The proposed method shows good results not only for estimating peak strength but also post-peak strength compared to previous experimental results. However, further research should be directed to improve the accuracy of the deformation modes.